2017
DOI: 10.1007/s11046-017-0161-5
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Profile of Aspergillus terreus Conidia at Germinating Stage: Identification of Probable Virulent Factors and Enzymes from Mycotoxin Pathways

Abstract: Aspergillus terreus is an emerging opportunistic fungal pathogen that causes invasive aspergillosis in immunocompromised individuals. The main risk group of individuals for this organism is leukopenic patients, individuals having cancers, bone marrow transplant persons and those who have immunological disorders. The lack of early diagnostic marker for A. terreus and intrinsic resistance to Amphotericin B, further limits the successful therapy of A. terreus-associated infections. The germination of inhaled coni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“… 19 , 22 Important factors affecting A. terreus virulence are inoculum size, host characteristics, 24 and the expression of terrelysin (a hemolytic protein), CgrA, CREB, PepP, MyoA, Mep, Hog1, and MPKC, secreted during germination of A. terreus conidia. 13 Remarkably, the rate of A. terreus infection increases proportionally with the pathogen inoculum, but inoculum size does not affect intrinsic host characteristics. 24 , 25 Therefore, it is important to understand key morphological aspects of PC and AC, and how they influence host colonization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 , 22 Important factors affecting A. terreus virulence are inoculum size, host characteristics, 24 and the expression of terrelysin (a hemolytic protein), CgrA, CREB, PepP, MyoA, Mep, Hog1, and MPKC, secreted during germination of A. terreus conidia. 13 Remarkably, the rate of A. terreus infection increases proportionally with the pathogen inoculum, but inoculum size does not affect intrinsic host characteristics. 24 , 25 Therefore, it is important to understand key morphological aspects of PC and AC, and how they influence host colonization.…”
Section: Resultsmentioning
confidence: 99%
“… 10 12 Given successful germination of A. terreus conidia is the key step to invasive aspergillosis, a recent proteomic study uncovered virulent proteins, such as Hog1 and MPKC, and high-level transcripts, such as the DHO and TER genes, associated with the transition stages that are a hallmark of conidia germination. 13 …”
Section: Introductionmentioning
confidence: 99%
“…at development stages (Asif et al 2006 ; Suh et al 2012 ; Tiwari et al 2016 ; Thakur and Shankar 2017 ). Comparative proteome analysis of resting conidia to mycelia provided biochemical and cellular pathway during the morphotypes of Aspergilli (Asif et al 2006 ; Vodisch et al 2009 ; Teutschbein et al 2010 ; Tiwari et al 2016 ; Thakur and Shankar 2017 ; Shankar et al 2018 ). To date, proteomic-based analysis on how Aspergilli adapt to host condition has conceded information of Aspergilli infection mechanisms (Suh et al 2012 ; Kubitschek-Barreira et al 2013 ).…”
Section: Proteomic Approach To Characterise the Antifungal Response Imentioning
confidence: 99%
“…But this technique has some limitations such as in the detection of low abundant proteins or resolution of large number of proteins. In last few years the shot gun approach has gained importance to carry out proteome analysis of Aspergilli at different conditions such as during morphological transitions to stress conditions (in exposure to antifungal or different carbon sources; Suh et al, 2012 ; Novodvorska et al, 2016 ; Tiwari et al, 2016 ; Thakur and Shankar, 2017a ). Such studies revealed the broad biological nature of these Aspergilli as well as their survival needed in the environment where they face multi-factorial challenges.…”
Section: Determinants To Exit Conidial Dormancymentioning
confidence: 99%
“…Recently, Thakur and Shankar reported proteins from germinating conidia or conidial proteins of A. terreus . A total of 42 conidial proteins were observed and majority of these proteins were from secondary metabolite biosynthesis, lipid metabolism and protein biosynthesis (Thakur and Shankar, 2017a ). Recently transcriptomic/translational study by Novodvorska et al demonstrated that A. niger conidia suspended in water have metabolic activity as compared to completely dried conidia.…”
Section: Determinants To Exit Conidial Dormancymentioning
confidence: 99%